How to verify the analytical and clinical performance of ELISA immunoanalysis in the real laboratory practice. PCSK9 as an example - Vacková, Tereza; Jabor, Antonín; Kubíček, Zdenek; Franeková, Janka (Journal of immunological methods, 2024)
BACKGROUND: Manufacturers and diagnostic companies often recommend on-site verification of analytical performance in the clinical laboratory. The validation process used by manufacturers is rarely described in detail, and certain information on analytical performance is missing from the product sheet, especially for immunoanalytical methods. We describe an approach to the detailed validation of an ELISA method for the measurement of proprotein convertase subtilisin/kexin type 9 (PCSK9) plasma concentrations. We compared manufacturers' claims of analytical performance with data obtained in the field laboratory using several approaches. METHODS: We used the Human Proprotein Convertase 9/PCSK9 Quantikine ELISA diagnostic kit (R&D systems, Bio-Techne Ltd., Abingdon Science Park, Abingdon, UK) and three levels of quality control solution Quantikine Immunoassay Control Group 235 (R&D systems, Bio-Techne Ltd., Abingdon Science Park, Abingdon, UK) to verify precision. We measured the concentration of PCSK9 using the DS2 ELISA Reader (Dynex Technologies GmbH, Denkendorf, Germany). We used analysis of variance (ANOVA) and the R statistical package (R core team, version 1.4.5). Statistical analysis and terminology were performed according to protocol CLSI EP15-A3, and the reference interval was checked according to CLSI/IFCC C28-A3c. RESULTS: We found a significant difference between the manufacturer's claims of analytical performance and real data measured in the routine clinical laboratory. The calculated CV (%) for repeatability (calculated by simple estimation of the mean and SD, as used by the manufacturer) was between 5.5% and 7.4%, but the manufacturer's claim was between 4.1% and 6.5%. Using ANOVA, the true repeatability was between 5.0% and 6.9%. Similarly, ANOVA revealed values of CV (%) for within-laboratory imprecision between 6.5% and 9.1%, while the manufacturer's claims were between 4.1% and 5.9%. The recovery ranged from 105.5% to 121.8%. The manufacturer's recommended reference interval was checked and we didn't find any significant difference between men and women. CONCLUSIONS: We describe a comprehensive approach to verify the analytical performance of an ELISA method using the measurement of PCSK9 plasma concentration as an example. We found differences between the results of this approach based on the CLSI EP15-A3 protocol and data provided by the manufacturer. We recommend the verification of analytical performance by more complex statistical tools in laboratory practice.
Keywords: proproteinkonvertasa subtilisin/kexin typu 9; Reproducibility of Results; Enzyme-Linked Immunosorbent Assay; lidé; reprodukovatelnost výsledků; Female; mužské pohlaví; ELISA; Male; Quality Control; Proprotein Convertase 9; reagenční diagnostické soupravy; ženské pohlaví; Reagent Kits, Diagnostic; řízení kvality; Humans